Pengaruh Model Pembelajaran Kooperatif Tipe Stad Terhadap Hasil Belajar Siswa Pada Materi Sistem Pertidaksamaan Linear Dua Variabel Di SMA N 1 Tabukan Selatan - Wembli Pebakirang (Journal on Education, 2023)
Department of Mathematics Education, Faculty of Mathematics, Natural and Earth Sciences. Tondano 2023. This research aims to determine the differences in student learning outcomes taught using the STAD type cooperative learning model and student learning outcomes taught using the conventional/lecture learning model on a two-variable linear inequality system. The research subjects were class XI MIA I which used the STAD type cooperative learning model and class XI MIA II used the Direct Instruction learning model. This research method is experimental, with a research design namely Randomized Subjects Posttest Only Control Group Design. Two classes were taken as samples, namely class XI MIA I as the experimental class and XI MIA II as the control class with a total of 30 students in each class. The research data were analyzed using the t-test and showed that the value of t_(count g) <t_table = 16.833 > 2.002 with a real level of α=0.05, this means rejecting H_0 and accepting H_1. Thus, the use of the STAD type cooperative learning model influences student learning outcomes in the material on systems of linear inequalities for two variables in class XI at SMA N 1 Tabukan Selatan.